The VALIDASI METODE DAN PENETAPAN KADAR FLAVONOID TOTAL SEDIAAN PEMBERSIH WAJAH ROSELLA BERBASIS AIR MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Fitri, Hidayah Anisa (Acta Pharmaceutica Indonesia, 2024)
Rosella flower extract is known rich in flavonoid anthocyanin that has activity as antipollutants. So it has potential to be developed as a facial cleansing products. On previous studies, the optimum formula of roselle flower extract facial wash gell and micellar water has been obtained as water-base cleansing face products. Analysis of the of chemical compounds in both formula is essential to be conducted in order to determine their flavonoid content for their quality evaluation. In the analysis process, validated method should be used to ensure the method is performed in accordance to its purpose. This study aimed to validate the method and analyze total flavonoid content in the optimum formula of facial wash gell and micellar water containing rosella flower extract. The research was conducted using a UV-Vis spectrophotometry and method's validity was determined by analyzing linearity, LOD, LOQ, precision and accuracy parameter. Based on the results of the validation, all parameters of the analysis tested were qualified. The total flavonoid content of facial wash gell and micellar water determined by the valid method were 0.482 ± 0.008 mg QE/g and 0.136 ± 0.001 mg QE/g.